"The Hellenistic ruler cult and Ptolemy I's quest for legitimacy" - Ntuli, Sihle (Rhodes University, Faculty of Humanities, School of Languages, 2017)
Alexander III died suddenly in Babylon in 323 BC. With Philip III Arrhidaeus in a mentally deficient state and Alexander IV not being of age, Alexander died without a suitable heir. The task of succeeding one of the most storied legacies in the ancient world was left to the generals of Alexander III. On his deathbed, Alexander was asked who should lead the Macedonians, of which he allegedly replied "the strongest" . Thus began the process of selecting the individual who would succeed Alexander the Great, which ended up becoming a contentious task due to Macedonian succession customs. Subsequently the 'Successors' quarrelled over who should succeed Alexander as the true successor. The wars of the Successors are founded on an issue of legitimacy that qualifies the notion of the strongest. Being deemed the true successor of Alexander the Great meant the opportunity to continue a period of Macedonian dominance following the reigns of Philip II and Alexander III. Alexander III is hailed as one of the most extraordinary individuals of the ancient world with his imperial campaigns being widely documented, political stability being pinpointed as one of the Macedonian strong points during the period of their dominance. The ruler cult is a point of reference for the explaining the relative political stability throughout the reign of Alexander the Great. The ruler cult can be understood as a sociopolitical construct that hybridized the notion of the ruler with that of a religious leader. The oriental influence of Alexander's campaigns in Asia would inform the customs and practices of the divine ruler. The Macedonians' ability to establish a presence in foreign territories made such a social construct a necessity in the task of centralizing of minds for political stability. Alexander's rendition of the cult informed the formalized Ptolemaic ruler cult. The similarities and differences of the renditions help us to understand this political tool that Ptolemy I required in order to be deemed the true successor of Alexander the Great. The following will be an investigation into whether Ptolemy I is able to attain legitimacy, firstly as a successor to Alexander the Great, secondly as Pharaoh of Egypt.
Keywords: Uncatalogued